The Shariah Governance in Palestinian Islamic Banks:A Professional Development Perspective - Tariq Alsayed Ahmad; Nehad Ibrahim Abd Alfatah Ineizeh; Zurina Shafii; Asharaf Mohd Ramli (Karya Ilham Publishing, 2025)
Karya Ilham Publishing , Volume 40 Issue 1 Page (40–46)